Kilka uwag o zwalczaniu korupcji w świetle prawa europejskiego i międzynarodowego - Płońska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
In today’s world, corruption is becoming increasingly supranational, which is why international cooperation in the fight against corruption is becoming increasingly important. The legislative work undertaken in connection with the internationalisation of anti-corruption criminal law is now regarded in the literature on the subject as one of the key means of fighting corruption. The aim of the article is to present the essence of the problem in the light of European and international law. In particular, the author focuses on explaining the definition of corruption and on presenting those forms of bribery that are treated as criminal offences by the Council of Europe’s Criminal Law Convention on Corruption. She also emphasises the importance of the UN Convention against Corruption to the prevention, detection and elimination of international transfer of assets obtained unlawfully from corruption, as well as the role of such anti-corruption institutions as the International Criminal Police Organisation Interpol, European Police Offi ce Europol, European Judicial Cooperation Unit, European Anti-Fraud Office OLAF and Group of States against Corruption GRECO.
Keywords: corruption; combating corruption; European law; international law